Kinetic modelling for COD and nitrate- N removal from hatchery wastewater through biological approach - Norazwina, Zainol; Nor Hazwani, Aziz; Nur Husnina, Mohamed Nor Rahim (EnPress Publisher, LLC, 2023)
This study was conducted to determine the nutrient removal efficiency via the application of mixed cultures from the synthetic hatchery wastewater based on the first-order, second-order and Stover Kincannon models. The synthetic wastewater was prepared according to the characterization of the collected hatchery wastewater sample, and the collected mixed cultures from the pond sediment were acclimatized accordingly. The samples were tested for chemical oxygen demand (COD) and nitrate-N concentration using a Hach spectrophotometer to determine the removal value of the nutrients. The findings show that the highest removal percentage for COD was up to 31.35% on day 3. Meanwhile, the highest removal percentage for nitrate-N was obtained on day 4 at 43.48%. The obtained correlation coefficient, R2 for COD through first-order, second-order, and Stover Kincannon models is 1, 0.6774, and 0.965, respectively, suggesting that the kinetics of COD removal can be described most properly by the first-order model. A similar model was also reported for nitrate-N with R2 value of 1, 0.7563, and 0.8693 for the first-order, second-order, and Stover Kincannon models, respectively. Based on the findings, the acclimatized mixed culture used in this study could be a potent natural COD and nitrate-N removal in the hatchery wastewater.